A magnetic controllable tool for the selective enrichment of dimethoate from olive oil samples: A responsive molecular imprinting-based approach - Garcia, Raquel (2018)
Aiming to develop a straightforward magnetic-based sample preparation methodology for the selective extraction of dimethoate from olive oil, the synthesis of dimethoate-imprinted polymer on the surface of modified magnetic nanoparticles has been attempted. Molecular recognition assays have proven their suitability for the selective pre-concentration of dimethoate. Mechanistic basis for template selective recognition has been explored using a quantum chemical approach, providing new insights about the mechanisms underlying template recognition. Thus, a magnetic molecularly imprinted solid-phase extraction method was developed allowing the extraction of dimethoate from spiked olive oil samples, at levels similar to the maximum residue limits imposed by legislation, followed by the quantification of their levels by high-performance liquid chromatography with diode-array detection. Recoveries of 94.55% were obtained, with relative standard deviations lower than 0.53% (n=3). The developed sample preparation technique enables a selective pre-concentration/enrichment of dimethoate from olive oil matrix with minimum handling and less solvent consumption.